Konteks Ancaman Keamanan Energi Arab Saudi Dalam Perspektif Sovereignty, Robustness, dan Resilience - Ammar, M. Almer (Jurnal Ilmiah Hubungan Internasional Fajar, 2025)
The drone attacks on Saudi Arabia's oil infrastructure in Abqaiq-Khurais in 2019 marked a critical turning point in national energy security strategy. This study analyzes the context of Saudi Arabia's energy security threats through three theoretical perspectives by Cherp & Jewell (2011): sovereignty, robustness, and resilience. Using a descriptive qualitative approach, the study identifies physical vulnerabilities of energy infrastructure due to extreme weather and domestic dependence on a single energy source (robustness), challenges to energy sovereignty such as U.S. dominance in arms procurement and economic dependence on oil exports (sovereignty), as well as adaptation efforts to geopolitical threats and cyberattacks (resilience). The findings show that Saudi Arabia has taken strategic steps, including export market diversification, development of renewable energy (e.g., NEOM Green Hydrogen project), investment in anti-drone technology, and strengthening of human resource capacity. However, the transformation toward a sustainable energy system still faces structural and geopolitical barriers. Keywords: Energy Security, Arab Saudi, Threat of Energy Security